The importance of cancer prevention policies to inform and guide preventative and screening measures for people with intellectual disabilities: The COST project “Cancer- Understanding Prevention in Intellectual Disabilities” - Vukovic, Vladimir; Banda, Amina; Carneiro, Lara; Dogan, Soner; Knapp, Peter; McMahon, Martin; Cuypers, Maarten (SAGE Publications Ltd, 2026)
Cancer is a global public health problem, but its exact prevalence in people with intellectual disabilities is still uncertain. This population, with limited health skills and complex health needs, faces many challenges in cancer prevention, screening, timely diagnosis and treatment. Furthermore, they are often underrepresented in general cancer prevention and screening policies across Europe, leading to widened disparities in health outcomes and premature mortality. Thus, unified national and local policies are needed to reduce inequalities and promoting a pan-European inclusion of people with intellectual disabilities. Our goal is to raise public awareness of this issue, including the involvement of people with intellectual disabilities, and promote engagement from relevant stakeholders. The COST Action ‘Cancer- Understanding Prevention in Intellectual Disabilities’ (CUPID) project will address health inequalities faced by people with intellectual disabilities in relation to cancer, and support the development of policy recommendations specifically tailored to their unique cognitive and healthcare needs, having a positive long-term impact on quality of life. © The Author(s) 2023. This article is distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 License (https://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage).
Keywords: cancer; intellectual disability; policy; prevention; screening